Internalizing Pluralism in Islamic Education: Boosting Religious Character at SMPN 46 and SMPN 2 Cileunyi, Bandung - Sahliah Sahliah; Uus Ruswandi; Ahmad Sarbini; Bambang Samsul Arifin; Dedi Junaedi (UIN Sunan Gunung Djati Bandung, 2026)
Modern society lives in an environment characterized by increasingly complex cultural, ethnic, and religious diversity due to the influence of globalization. This condition demands that the education system, especially Islamic Religious Education (PAI), adapt so that it does not only emphasize ritual and dogmatic aspects, but also fosters mutual respect, empathy, and tolerance between religious communities. Without a pluralism-based approach, PAI learning has the potential to become rigid and less relevant to the social reality of students. Therefore, it is essential to incorporate pluralistic values, such as respect for differences, compassion, and cooperation, into the learning process from an early age. This principle aligns with QS. Al-Hujurat verse 13 which emphasizes the importance of recognizing and respecting diversity. Teachers play a role as facilitators in creating an inclusive, reflective, and dialogical learning environment, so that the values of pluralism can be internalized naturally in students. This research employs a qualitative approach, utilising case studies at SMPN 46 Bandung and SMPN 2 Cileunyi. The research results show that the internalization of pluralistic values in Islamic Religious Education (PAI) learning occurs systematically, contextually, and effectively through experience-based learning activities, teacher role models, and a supportive school culture. This process successfully shapes students' religious character to be tolerant, inclusive, and virtuous. Therefore, pluralistic character education in PAI is a crucial strategy in preparing a religious generation capable of living harmoniously in a diverse and dynamic society.